Goodwill e valor econômico de uma empresa: uma proposta - Gomes, Marli (2013)
This study aims to investigate the rules that establish the relationship of the record of intangible assets generated in corporate reorganizations, by ways of consolidation, spin-off, merger and, especially, of goodwill, facing the changes in the standards currently adopted by the Brazilian accounting system, which in addition to following global trends, also adopts all recent legislative changes. As a methodological option, the research is qualitative, of the exploratory-descriptive type, and promotes the analysis of a proposal to Company Beta, a fictitious name, in relation to the goodwill generated by the merger, as well as the limits that rule the possibilities of registration, measurement and amortization of such goodwill, for tax purposes. Indirectly, this study demonstrates the need to regulate the accounting standards and procedures relating to the measurement criteria of the established goodwill, so as to bring it to more realistic levels, based on objective and reliable principles. Similarly, this research aims to analyze the issue of goodwill, through concepts of Corporate Transactions and Business Combinations, as well as Intangible Assets and their measurement. Based on this study it was possible to measure the potential for the generation of wealth from Company Beta s business for decision making and also to determine the goodwill value from the analysis of financial statements and projections of the Company. The proposed objectives were achieved and the goodwill value presented reinforces the importance and the relevance of the record of intangible assets